Research and application of the mathematical model for extreme weather event in coastal urban areas - Li, Chaochao; Huang, Miansong; Tian, Juncang; Isabella Anak Gisen, Jacqueline (Elsevier Ltd, 2022)
Extreme weather event simulation in coastal urban areas is more complex and difficult due to their special geography and climate characteristics, different kinds of land uses, close-packed buildings, and large amounts of flood control works and drainage systems. Urban Flood Simulation Model (UFSM) was integrated in this study to simulate the extreme weather events in the Pudong flood protection area (Shanghai, China). The model is established based on two-dimensional unsteady flow theory and nonstructural and irregular mesh technique. A method based on one-dimensional unsteady flow theory is proposed to deal with small-scale river and road. The calculation of the pumping stations, the water gates is indicated based on the real scheduling discipline. The extreme weather event scenarios (typhoon+rainstorm+ astronomical high tide + upstream flood) are simulated. The results show that the flood risk is higher in the coastal area and the upstream of the Huangpu Rive, and UFSM is a suitable method for simulating the flood inundation of coastal urban areas.